Relations between the Lithuanian Government and the Baltic Military District and its Garrisons in 1946–1962 - Kšanytė, Raminta (Genocidas ir rezistencija, 2005)
Historiography in the Western countries has directed most attention on the relations between the Soviet army and the Communist Party. Until now, no one has substantially investigated the influence which the army of occupation exerted on the Soviet-annexed Lithuania, nor has analysed the relations between the Soviet army and the local authorities. A study of the vast archival materials of 1945–1962 establishes that the influence of the occupying army in Lithuania was exerted through the relations between the military authorities and the local state institutions. The demands of the military also depended on the Soviet military doctrine, according to which the divisions were deployed and new military bases (including nuclear ones) were established, or by contrast, which military divisions were disbanded and which military units were demobilised. Changes in military doctrine forced the Soviet authorities to look for ways to meet the changing military and military-social demands by using local resources. The demands of the military were realised mostly by means of local resources and were related to the allowances of land (in various forms, the occupying army owned about six percent of all the land in Lithuania), premises, housing, and food. In 1955–1956 and 1960–1962, the social costs of the military reform were placed on the local authorities; the military’s relations with local authorities depended on the housing demands of the army. The housing problem was partly solved by utilising the property of deported Lithuanians, and establishing the "10 percent fee", paid in kind, on the reconstruction and construction of apartments for the benefit of the military, and also developing the mass construction works in 1960–1961. As a result of the new military doctrine developed in preparation for a possible sudden attack of the NATO states from the air and the possible use of the nuclear weapon, Lithuania was forced to implement all the war plans adopted in Moscow. To implement those plans the local authorities were forced to cooperate closely with the military structures. The increasing interdependence of the military and local authorities was reinforced by Nikita Khrushchev through his military reforms – involving leaders of the local party nomenklatura in military councils and giving the Party more rights in dealing with military issues. The local authorities in Lithuania were continuously getting more involved in the implementation of the law on the general national service. Control of the implementation of the Soviet universal military service and the carrying out of the requisite policies greatly increased the Party’s control of the military – a major goal of Khrushchev’s military reforms.